The Glass Cafe, or, The stripper and the state how my mother started a war with the system that made us kind of rich and a little bit famous - Paulsen, Gary 1939-2021 (Wendy Lamb Books, 2003)
When twelve-year-old Tony, a talented artist, begins sketching the dancers at the Kitty Kat Club where his mother is an exotic dancer, it sparks the attention of social services